Biochemical and computational insights of adenosine deaminase inhibition by Epigallocatechin gallate. (December 2019) - K.G, Arun; C.S, Sharanya; J, Abhithaj; C, Sadasivan
Graphical abstract: Highlights: Adenosine deaminase inhibitory activity of Epigallocatechin gallate is evaluated. Inhibition assay indicated that the compound significantly reduced ADA activity. As per ITC data, the binding free energy is −6.84 Kcal mol −1 . The binding is also confirmed by fluorescence spectrometry study. In silico studies revealed the structural details of binding. Abstract: Epigallocatechin gallate, a flavonoid from Camellia sinensis possess various pharmacological activities such as anticancer, antimicrobial and antioxidant etc. Adenosine deaminase, (ADA), is a key enzyme involved in the purine metabolism, the inhibitors of which is being considered as highly promising candidate for the development of anti-proliferative and anti-inflammatory drugs. In this work we studied adenosine deaminase inhibitory activity of epigallocatechin gallate by using biophysical and computational methods. The enzyme inhibition study result indicated that epigallocatechin gallate possess strong inhibitory activity on ADA. ITC study revealed the energetics of binding. Also the binding is confirmed by using fluorescence spectroscopy. The structural details of binding are obtained from molecular docking and MD simulation studies.